LEVELS OF SOURNESS, BITTERNESS AND SWEETNESS OF CHOCOLATE PRODUCTS ON CONSUMER ACCEPTANCE (CASE STUDY IN THE SPECIAL REGION OF YOGYAKARTA, INDONESIA) (Jurnal Teknologi Industri Pertanian, 2026)
In Indonesia, chocolate products are often associated with high sweetness, leading to distorted consumer perceptions of couverture chocolate, which ideally balances acidity, bitterness, and sweetness. This study aimed to evaluate consumer acceptance of six chocolate couverture formulations in the Special Region of Yogyakarta (DIY) and identify the most preferred formulation based on a balanced sensory profile. Using convenience sampling, 500 untrained panelists aged 15–60 years were selected across five districts in DIY Province. Participants evaluated sweetness, bitterness, acidity, aroma, texture, and overall acceptability through hedonic and ranking tests. Physicochemical parameters (pH, viscosity, and hardness) were also measured to support sensory findings. Results showed that formulations F1 and F2 achieved the highest overall acceptability scores due to moderate bitterness and acidity, preferred sweetness, and smoother texture. The ranking test confirmed these results, with F1 and F2 recording the lowest mean ranks. Physicochemical analysis supported these findings, showing higher pH (6.68 and 6.63), moderate viscosity (6,580 and 5,140cP), and lower hardness (46.83 and 50.52 N). Consumer age significantly influenced preference, with younger respondents favoring sweeter and softer chocolate. These findings emphasize the importance of optimizing sensory and textural attributes to meet diverse consumer expectations.Keywords:  consumer acceptance; consumer preference; chocolate; sensory evaluation